Reverence, resistance and politics of seeing the Indian national flag - Sadan Jha (Cambridge University Press India, 2016)
"Charts a history of the national flag of India in colonial and post-colonial periods and looks at the politics that go into the making of various discourses and ways of looking at the Indian national flag"--